2006
DOI: 10.1073/pnas.0510863103
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of two hereditary spastic paraplegia gene products, spastin and atlastin, suggests a common pathway for axonal maintenance

Abstract: Hereditary spastic paraplegia (HSP) is a neurodegenerative disorder that is characterized by retrograde axonal degeneration that primarily affects long spinal neurons. The disease is clinically heterogeneous, and there are >20 genetic loci identified. Here, we show a physical interaction between spastin and atlastin, two autosomal dominant HSP gene products. Spastin encodes a microtubule (MT)-severing AAA ATPase (ATPase associated with various activities), and atlastin encodes a Golgi-localized integral membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
107
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 24 publications
2
107
0
Order By: Relevance
“…There are two major forms of spastin in mammals; the longer M1 spastin contains a hydrophobic domain and is abundant only in brain and spinal cord (21), whereas the soluble M87 form is ubiquitous. M1 spastin, but not M87, interacts with REEP1, atlastins, and reticulons at the ER (11,22,23). Because only M87 spastin is detectable in cultured cells, we were unable to examine the endogenous interaction of protrudin with M1 spastin.…”
Section: Significancementioning
confidence: 98%
“…There are two major forms of spastin in mammals; the longer M1 spastin contains a hydrophobic domain and is abundant only in brain and spinal cord (21), whereas the soluble M87 form is ubiquitous. M1 spastin, but not M87, interacts with REEP1, atlastins, and reticulons at the ER (11,22,23). Because only M87 spastin is detectable in cultured cells, we were unable to examine the endogenous interaction of protrudin with M1 spastin.…”
Section: Significancementioning
confidence: 98%
“…On a microscopic level, they are found to associate with three-way junctions in the ER, and their absence results in a loss of this morphology in exchange for long, unbranched tubules (14,20). At the ER, atlastin interacts with proteins from the reticulon and DP1 families (14), spastin/SPG4 (21,22), and REEP1/SPG31 (20). Notably, members of these families have been found to be among the most frequently mutated loci in the neurodegenerative disorder hereditary spastic paraplegia (HSP; also known as familial spastic paraplegia or Strumpell-Lorrain disease) (23).…”
mentioning
confidence: 99%
“…One of the major players involved in ER shape is the membrane fusion protein Atlastin (6). We and others have shown that the GTPase Atlastin drives the fusion of ER tubules and that this fusion reaction is vitally important for the overall function of this organelle (6, 7) Atlastin interacts with a variety of other proteins resident within the ER, like the ER shapeforming proteins reticulon, receptor expression-enhancing protein (REEP), and DP1 (7); spastin (8,9); and luna park (10).…”
mentioning
confidence: 99%